Fabrication of gas-permeable polyvinylidene fluoride (PVDF) hollow-fiber membrane by dry-jet wet spinning and its application in membrane biofilm reactors - Aksoy, Yunus; Hasar, Halil (Elsevier, 2021)
This study presents the usability of produced gas-permeable hollow fiber membranes in a membrane biofilm reactor. Different morphologies of the membranes were obtained by adding poly(vinylpyrrolidone) or propionic acid to the dope solution during the fabrication step. It was found that contact angles and oxygen-gas diffusion coefficients membranes with additives increased compared to the pristine membrane as Young's modulus decreased. The membrane with the highest oxygen gas diffusion coefficient (5 wt% PVP K10) was tested in hydrogen and oxygen-based membrane biofilm reactors (MBfRs) in terms of nitrate reduction and ammonium oxidation, respectively. The results showed that H-2-based MBfR achieved nitrate flux of 3.31 g N/m(2). d while the flux of H-2 utilized for NO3-N reduction was 1.18 gH(2)/m(2). d. On the other hand, the flux of NH4-N was 6.16 g N/ m(2). d while the flux of O-2 utilized for NH4-N oxidation reached to a maximum value of 28.14 gO(2)/m(2). d in the O-2-based MBfR system. The results showed that the hollow fiber gas-permeable membrane fabricated by dry-jet wet spinning method with poly(vinylpyrrolidone) or propionic acid as additives of dope solutions could be an inexpensive approach to make it prevalent the membrane biofilm technology.
Keywords: Gas-permeable membrane; PVDF hollow fiber; Dry/jet wet spinning; Membrane biofilm reactor